Pengaruh TAM Terhadap Keputusan Mahasiswa Universitas Raden Mas Said Surakarta Dalam Sistem Pembayaran Gopay Pada Layanan Gojek - Kholifah Yasinta Anwar; Agus Setiawan; Fitriyah Hasna Putri Winargo (LPPM - STIE SAKTI ALAM KERINCI, 2023)
Gojek is present as an e-commerce leader in the transportation system provide convenience to consumers in Indonesia. Gojek continues to grow difficulties faced by consumers when using the application, so that consumers feel comfortable using the application. One of the innovations issued by Gojek is known to consumers as the gopay payment system as a solution when consumers do not carry cash and are lazy to pay for cash transactions. The Technology Acceptance Model (TAM) involves consumer decisions in using the gopay payment system in this study explaining perceived usefulness, perceived convenience, customer satisfaction and client attitudes. The research method used included the use of primary data, primary data. This was achieved by distributing questionnaires to consumers who responded to the gopay payment system in the gojek application at least five times with the gopay payment system in the gojek application to 96 gojek consumers using random sampling techniques during the time this research was conducted. The analysis tool used is Smartpls. The results of the study show that perceived benefits, perceived convenience, consumer attitudes have a significant influence on consumer decisions on the gopay payment system for gojek services in Surakarta